Baseline survey report on birth preparedness Siraha district Nepal. (2002)
EXECUTIVE SUMMARY: This report is based on the survey conducted in Siraha district with the objective of collecting benchmark data on antenatal, delivery and postpartum care, maternal nutrition, new born care, child survival, and birth preparedness. These indicators will assess the changes observed after the implementation of the Saving Newborn Lives birth preparedness program planned in the district. Save the Children US will implement this program in partnership with the centre for Development and Population Activities (CEDPA). The data was collected in september 2002. In 27 systematically selected VDCs and 2 municipalities, a total of 299 women who had given birth in the last one-year period were interviewed using structured questionnaire. The mean age of respondents was 24.9 years and although a third could not state their age, the majority of those who could were in their twenties. By ethnicity, the largest percentage (33.1%) were Shaha/ Teli/ Koiri/ Mahato/Mandal, followed by yadav (17%),Damai/Kami/Chamar/Musahar/Dusad (15%),and Chaudhary (13.4%). Three-fourths of the respondents were illiterate. About two-thirds of the women reported receiving antenatal care during last pregnancy. Slightly over half had received antenatal care from a skilled provider. Nearly two-thirds received counseling in two or more areas. Based on ANC cards and reported history, the total percentage of mothers who had received at least two doses of TT was estimated at over 80%. A relatively high number (67.9%) could name at least two conditions during pregnancy that indicate a woman needs to seek immediate health care. The vast majority (88.3%) of deliveries were conducted at home, with untrained friends/neighbors/relatives attending 63.1% of these births. Skilled assistance in delivery was found to be 16.9% while assistance from a trained providers was 16.7%. The percent of mothers who knew at least two danger signs during labor and delivery was 64.2%. Forty-four percent of the mothers had received some kind of health service or advice after they had given birth to their last child. Of the women who received postpartum care, 71.6% received care within one week of delivery. The person who provided this kind of care was in most cases (45.0%) a relative, friend or neighbors. Less than a quarter (21.5%) received postpartum care from skilled providers. Eighty percent of mothers who received postnatal care were counseled I two or more areas. Almost half(46.3%) if the respondents received Vitamin A within six weeks of delivery and a slightly smaller number (41.2%) reported taking iron tables. Thirty percent of the mothers who gave birth at home reported using a clean home delivery kit. Out of the total number of deliveries, the percentage using a clean instrument to cut the cord was found to be 96.3%. Over half of the women reported that their last baby had been dried placenta was delivered and almost an identical number said the baby had been wrapped in cloth before the placenta was delivered. Seventy percent of the babies were bathed within an hour after delivery. Less than half of the women received any newborn care of advice. Of those that did, about 90% received counseling on breastfeeding, 88% on keeping the baby warm, and 60% on danger signs. Out of the total respondents,57.5% could state at least two danger signs in newborns. Almost all ( 95.3%) of the participants had breastfed their last child. However, only 62.8% gave colostrum to the baby and 56.9% also gave the baby something else to eat or drink before feeding breast milk. After one month, only about half of the babies were exclusively breastfed. Over seventy percent of the respondents had made preparations for someone to assist with the delivery of their last child, most commonly a relative, friend, or neighbor. Two-thirds had planned for the place of delivery, with 81.5% selecting their own home as the place of delivery, followed by 15.9% who planned to deliver at a hospital. Nearly 63% of the mothers had made financial preparations for the delivery of their last child through means including saving a little by little, taking loans, and doing extra work. Slightly less than half made plans in case of an emergency. Almost exactly half had made preparations for postnatal and newborn care. Most often these preparations concerned finances and food.